Initiating a district-based public-private mix to overcome tuberculosis missing cases in Indonesia: readiness to engage - Deni Kurniadi Sunjaya; Cindra Paskaria; Dewi Marhaeni Diah Herawati; Meisera Pramayanti; Rini Riani; Ida Parwati (BMC, 2022)
Abstract Background District-based public - private mix (DPPM) is a variant of a relatively new PPM strategy of addressing missing cases in the tuberculosis (TB) care cascade in Indonesia. We aimed to determine the readiness of various stakeholders to engage in implementing the DPPM strategy. Methods The research design was sequential exploratory mixed methods. A qualitative study in the first stage was carried out through in-depth interviews, FGD and study documents. Data were analyzed through coding, categorizing, pattern matching and theorizing. The second stage was a survey conducted using instruments built in the first stage. Data were analyzed using Rasch modeling and logistic regression. Results District TB case detection rate (CDR) has improved from 35% (2018) to 104% (2019). The contribution of private hospitals has increased considerably. However, there were almost none from the private primary healthcare facilities. The substantive theory generated indicates that awareness and concern of the TB problem, TB program comprehension and involvement, and institutional support are behind the readiness of facilities to engage the TB program (the readiness to engage). The measurement results indicate the significant correlation of all dimensions on readiness to engage. Concern of the TB problem and institutional support are variables that influence readiness to engage (p < 0.05). Conclusions Engaging private and public facility stakeholders is a challenge for local government. Intervention is through a personalized approach, encourages institutional support of health facilities for the TB program and system approach.